Leadership as an Institutional Mechanism: Academic Quality Formation in State Islamic Higher Education Institutions - Riyuzen Riyuzen; Zainal Arifin; Nurul Hidayati Murtafiah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
Leadership studies in higher education remain largely dominated by perspectives that treat leadership as a set of individual styles, traits, or behavioural attributes. Such approaches often assume a relatively direct relationship between leadership and academic quality, while giving less attention to the institutional processes through which leadership is organised and sustained. This study examines how leadership operates as an institutional mechanism in shaping academic quality in State Islamic Higher Education Institutions in Indonesia. Using an explanatory mixed-methods design with a comparative case study orientation, the research was conducted at UIN Raden Intan Lampung and UIN Sunan Kalijaga Yogyakarta. Quantitative survey data were used to map perceived leadership orientations. In contrast, qualitative interviews, observations, and document analysis were used to explain how leadership was enacted through governance, policy coordination, and quality assurance practices. The findings show that democratic, transformational, servant, and transactional orientations appear in hybrid and context-dependent forms, whereas authoritarian and laissez-faire orientations remain marginal. These patterns are better understood as institutional responses to organisational history, developmental phase, governance configuration, and strategic priorities than as expressions of leaders’ personal preferences. Academic quality emerges not directly from particular leadership styles, but from leadership translated into governance arrangements, academic policies, internal quality assurance systems, and coordinated institutional routines. The comparison further indicates that leadership mediation takes different forms across the two institutions. The study thus shifts attention from personalistic and linear explanations toward a more contextual understanding of leadership in complex academic settings.